Meat production on savannah-like graálands (dehesas) in semi-arid zones of the province of Salamanca - Martin Polo, J.L.=700 1 Garcia Bellido, I.; Sanchez Rodriguez, E.
(Es, En)
ilus., 26 ref.
Keywords: GANADO; MANEJO DEL GANADO; CARGA GANADERA; PRODUCCION DE CARNE; MANEJO DE PRADERAS; PASTIZALES; VALOR ENERGETICO; ESPAÑA